Teacher Title System and Teacher Empowerment in China - Ying Zhang; Kwok Kuen Tsang (New Zealand Journal of Teachers' Work)
The teacher title system is a strategy used by China government to cultivate teacher professionalization. Although teacher empowerment is an essential component of teacher professionalization, few studies have investigated the impact of the teacher title system on teacher empowerment in order to evaluate the effectiveness of the teacher title system. Thus, the study examined the relationship between the teacher title system and teacher empowerment by surveying 262 primary and secondary schoolteachers in a city in Liaoning Province. The findings suggest that the teacher title system might insufficiently empower teachers in China. Implications for teacher professionalization in China are discussed and suggestions for further studies are also addressed.